Outcome of Percutaneous Modified Catheterization Technique for Treatment of Types 2 and 3b Hepatic Echinococcal Cysts - Karaagac, Seda Sogukpinar; Durmaz, Hasan Ali (Springeropen, 2025)
This study aimed to determine the efficacy and success of the percutaneous modified catheterization technique (Mo-CAT) in treating type 2 and 3b liver cystic echinococcosis (CE). A total of 21 patients (13 female, 8 male) aged 23-78 years (median, 35 years) with 25 cysts were included. All cysts were catheterised (12-16 F) under imaging guidance. The daughter cysts and membranes were destroyed by manipulation of the catheter and wire. Repeated injection and reaspiration with small volumes (5-10 ml) of hypertonic or isotonic saline. Daughter cysts, endocysts, and non-drainable material were aspirated. Seventeen of the 25 CE cases (68%) were associated with the biliary system, and eight cysts were not. The procedure was terminated by withdrawal of the catheter after cyst collapse and aspiration of all materials. The median duration of catheterization was 60 days (min:15, max:120) in the case of cystobiliary fistula (CBF) and 5 days (min:4, max:10) in the case without a fistula (p < 0.001). All patients were treated with 96% technical success (24 cysts). While the volume reduction was 100% in 18 cysts, the median volume reduction in 7 cysts was 90% (min: 25%, max: 98%). Patients were followed-up for a median of 18 months after treatment (min: 6, max: 42), with no recurrence in 96% of patients. The treatment of liver CE 2 and 3b with the Mo-CAT technique is effective and safe when performed under appropriate technical conditions. It has been shown to be more helpful than surgical treatment for reducing hospitalization and preventing complications.
Keywords: CE2 and CE3b; Modified catheterization; Liver; Percutaneous treatment